THE INFLUENCE OF EPA «PROAKTYVO» AND FA «EMBIOTIK» ON THE LEVEL OF STRENGTH OF THE IMMUNITY OF CALVES - Rybachuk, Zh. V.; Lisnevskiy, A. R.; Bezditko, L. V. (Scientific Progress & Innovations, 2022)
The article presents the results of the use of enzyme-probiotic additive «ProAktyvo» and feed additive «EMBiotik» for calves aged 3–4 months, which were kept on a livestock farm unfavorable for infectious diseases with respiratory syndrome and without vaccination. It was found that the inclusion in the diet of these animals «ProAktyvo» at a dose of 3–4 grams daily for 21 days caused a tendency to reduce the content of immunoglobulins in serum by 5 % compared to the control group, in particular to 15.7±1 g/l. In calves, a decrease in cough intensity, appetite improvement, chewing gum intensity and hair condition was recorded. At the same time, in the control group, the clinical condition was unchanged or worsened (slight general depression, frequent wet cough). After 21 days of daily use of feed additive «EMBiotik» at a dose of 20 cm3 in 60 % of calves, the content of immunoglobulins in the serum exceeded 11.5 %, 20 % of calves – 50 % maximum physiological limit and 20 % vice versa – 22.2 % was less than the minimum physiological value. In general, the content of immunoglobulins in the serum was significantly (P≤0.05) higher than in the control group. At the same time, the animals receiving «EMBiotik» had improved digestive function, but the symptoms of inflammation of the upper respiratory tract increased, which necessitated the use of «Trifuzol 1 %» intravenously at a rate of 1 cm3 per 10 kg body weight for 3 consecutive days. After three days of complex therapy, the animals were clinically healthy. It was also found that in the calves of the experimental groups before feeding «ProAktyvo» and «EMBiotik» the content of immunoglobulins was at the same level: 17±1.2 g/l and 16.6±1.5 g/l, respectively. After 21 days of inclusion in the diet of EPA «ProAktyvo» registered their reduction to 15.7±1 g/l. In calves that received «EMBiotik» daily, the content of immunoglobulins significantly (P≤0.05) increased 1.2 times, which is 4 % higher than the maximum reference values. There was also a significant (P≤0.05) difference in the content of immunoglobulins in calves of the experimental groups. In particular, the average rate of the group of animals treated with «EMBiotik» was 32.5 % higher than that of calves receiving the enzyme-probiotic additive «ProAktyvo». Thus, the inclusion in the diet of calves of enzyme-probiotic additive «ProAktyvo» and feed additive «EMBiotik» provided improved digestive function and a tendency to reduce («ProAktyvo») or a significant (P≤0.05) increase (P≤0.05) increase («EMBiotik») content of immunoglobulins in the blood serum of calves aged 3–4 months.